Marbling Texture Does Not Affect Consumer Preference of Beef Strip Loin Steaks - K. R. Vierck; J. M. Gonzalez; T. A. Houser; E. A. Boyle; T. G. O'Quinn (Kansas Agricultural Experiment Station Research Reports, 2017)
In the beef industry, U.S. Department of Agriculture quality grades and marbling levels have long been associated with beef palatability and eating experience. Marbling score and maturity are the two major components of USDA quality grade. Traditionally, marbling texture has not been considered a factor of marbling score; however, there are often discernments at both the packer and retail level, as more than 75% of branded beef programs supervised by USDA-AMS have a specification of fine or medium textured marbling (USDA, 2015). Additionally, in some cases, fine and medium textured steaks are graded higher than their coarse counterparts, which results in a loss of possible premiums for producers and packers. There is very little research evaluating marbling texture and its effect on palatability and eating experience.
Keywords: marbling; consumer; palatability